Transforming Loyalty - Renee Rolle-Whatley; Kara Vander Linden (Grounded Theory Review: An International Journal, 2021)
The experiences of parents who daily participate in the rearing of their children framed this investigation into the maturation of selflessness using Glaser’s classic grounded theory. The theory reveals vulnerabilities, lessons, and rewards gleaned from continuous immersion in parenting. Viewed as a process, transforming loyalty discloses the circuitous route parents travel as parenting experiences shift focus towards a broadened awareness about the impact of allegiance and trust in caregiving. Releasing self-interest, embracing detachment, and living nonattached define transforming loyalty. In releasing self-interest, emotional balance eases egocentric perspectives; in embracing detachment, maturing selflessness validates the autonomy of others; and in living nonattached, emotion regulation heralds a broadened self-in-relationship. As egocentricity is confronted through engaged parenting, loyalty evolves to reveal the hidden gem of the parenting process—self-acceptance— conceptualized as a growth continuum transitioning loyalty to self into loyalty to family and onward towards a loyalty to all life.